Optimasi Penentuan Menu Makanan Pendamping Air Susu Ibu Menggunakan Algoritma Genetika - Wardatus Sa'adah; Umi Chotijah (Maranatha University Press, 2022)
Indonesia has a bad situation in stunting. Stunting is a problem because of the consumption of less nutrition. This is caused by giving food that is not in accordance with the nutritional needs of infants. Infants 0 until 24 months old need attention in choosing a weaning food to support the baby’s growth. The purpose of this research is to find an optimized way to improve the menu of weaning food with the genetic algorithm method. It is expected to be able to reduce stunting suffering in Indonesia. The process of the genetic algorithm method uses the fitness function of a baby’s daily nutritional needs. The selection is Roulette wheel selection method, the crossover is whole arithmetic crossover with 0.5 crossover rate, and the last is the mutation process with 0.6 mutation rate. The research used 100 generations and the result is menus for breakfast, lunch, and dinner for 6 days. The genetic algorithm can determine optimal weaning food’s menu.